2013
DOI: 10.3402/snp.v3i0.20770
|View full text |Cite
|
Sign up to set email alerts
|

Sexual desire, not hypersexuality, is related to neurophysiological responses elicited by sexual images

Abstract: BackgroundModulation of sexual desires is, in some cases, necessary to avoid inappropriate or illegal sexual behavior (downregulation of sexual desire) or to engage with a romantic partner (upregulation of sexual desire). Some have suggested that those who have difficulty downregulating their sexual desires be diagnosed as having a sexual ‘addiction’. This diagnosis is thought to be associated with sexual urges that feel out of control, high-frequency sexual behavior, consequences due to those behaviors, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 73 publications
(87 reference statements)
7
50
0
1
Order By: Relevance
“…Contrary evidence suggests that hypersexuals may not exhibit more sexual desire. No relationship between neural (P300) responses to sexual images and three measures of hypersexuality could be identified in a study sufficiently powered to detect small effect sizes (Steele, Prause, Staley, & Fong, 2013). Another study of 120 men and women did not identify any differences in the level of sexual arousal reported to sexual films between those reporting problem use of VSS and controls .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Contrary evidence suggests that hypersexuals may not exhibit more sexual desire. No relationship between neural (P300) responses to sexual images and three measures of hypersexuality could be identified in a study sufficiently powered to detect small effect sizes (Steele, Prause, Staley, & Fong, 2013). Another study of 120 men and women did not identify any differences in the level of sexual arousal reported to sexual films between those reporting problem use of VSS and controls .…”
Section: Introductionmentioning
confidence: 95%
“…Finally, those with more sexual intercourse partners exhibit greater LPP responses to sexually explicit images . However, the only study of neural sensitivity to sexual cues in those with problems regulating their viewing of VSS failed to find a relationship (Steele et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Further, it has been suggested that pornography has the potential to alter brain structures permanently, with the developing brain being the most vulnerable [57,58]. Because of current inconsistent neurobiological findings linking sexual images and behaviors with brain activity, more research in this area is needed [17,59].…”
Section: Discussionmentioning
confidence: 99%
“…These later aspects of the ERP waveform have been attributed to cognitive processes such as attention and working memory (P300) [25] as well as sustained processing of emotionally-relevant stimuli (LPP) [26]. Steele et al [14] showed that the large P300 differences seen between viewing of sexually explicit images relative to neutral images was negatively related to measures of sexual desire, and had no effect on participants' hypersexuality. The authors suggested that this negative finding was most probably due to the images shown not having any novel significance to the participant pool, as participants all reported viewing high volumes of pornographic material, consequently leading to the suppression of the P300 component.…”
Section: Physiological Effects Of Pornographymentioning
confidence: 99%
“…Studies utilizing ERP data tend to focus on later ERP effects such as the P300 [14] and Late-Positive Potential (LPP) [7,8] when investigating individuals who view pornography. These later aspects of the ERP waveform have been attributed to cognitive processes such as attention and working memory (P300) [25] as well as sustained processing of emotionally-relevant stimuli (LPP) [26].…”
Section: Physiological Effects Of Pornographymentioning
confidence: 99%